Experiential and Interpersonal Meanings in Women Leader’s Discourses on Covid-19: A Case on Jacinda Ardern and Tsai Ing-wen - Nasution, Laila Syafrina (Utamax : Journal of Ultimate Research and Trends in Education, 2021)
This article aimed to study Experiential and Interpersonal Meaning which was found in the discourses of the New Zealand Prime Minister. Jacinda Ardern on March, 23rd 2020, and President of Taiwan, Tsai Ing-wen on January, 30th 2020 related to covid-19. The objective of this study is to discover Experiential and Interpersonal Meaning in the discourse analysis context. This present study tried to highlight the best method to adopt for this investigation by employing the four steps proposed by Miles, Huberman, and Sadana's qualitative research method (2014), i.e., data collection, data condensation, data display, and conclusion drawing and verification. The results of the study showed that the Material process was prominent in the Experiential Meaning in discourses by 67.23%, The elements of participant's material process in participants were dominant by 54.61%, and location (27.435) was prominent in circumstances elements. Meanwhile, Subject was prominent in the Interpersonal Meaning in Mood Types by 52.47%, and Predicator (52.01%) was dominant in Residue Types. These highlighted how we can learn from these two female leaders in delivering suggestions, reminders, and persuading society during this Covid 19 pandemic.